Rethinking the measurement of the middle class: Evidence from Egypt - Khalid Abu-Ismail; Niranjan Sarangi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The degree of choice households have over their consumption expenditure is critical in deciding their economic class. Applying our measure to Egyptian household budget surveys, we estimate the population size of the middle class in Egypt and assess their well-being in the period 1995-2011. Our findings show that if economic growth is pro-poor and inclusive, more people at the lower end of income distribution will graduate into the middle class category. The increase in poverty rates and decline in the size of the middle class since 2005 indicates that the growth process in Egypt was anti-poor and anti-middle class.
Keywords: D63; E21; I32; B41; 330; consumption expenditure; inequality; measurement; middle class; poverty